Amphistomy: stomata patterning inferred from 13C content and leaf-side-specific deposition of epicuticular wax - Askanbayeva, Balzhan; Janová, Jitka; Kubásek, Jiří; Zeisler-Diehl, Viktoria V; Schreiber, Lukas; Muir, Christopher D; Šantrůček, Jiří (Annals of botany, 2024)
BACKGROUND AND AIMS: The benefits and costs of amphistomy (AS) vs. hypostomy (HS) are not fully understood. Here, we quantify benefits of access of CO2 through stomata on the upper (adaxial) leaf surface, using 13C abundance in the adaxial and abaxial epicuticular wax. Additionally, a relationship between the distribution of stomata and epicuticular wax on the opposite leaf sides is studied. METHODS: We suggest that the 13C content of long-chain aliphatic compounds of cuticular wax records the leaf internal CO2 concentration in chloroplasts adjacent to the adaxial and abaxial epidermes. This unique property stems from: (1) wax synthesis being located exclusively in epidermal cells; and (2) ongoing wax renewal over the whole leaf lifespan. Compound-specific and bulk wax 13C abundance (δ) was related to amphistomy level (ASL; as a fraction of adaxial in all stomata) of four AS and five HS species grown under various levels of irradiance. The isotopic polarity of epicuticular wax, i.e. the difference in abaxial and adaxial δ (δab - δad), was used to calculate the leaf dorsiventral CO2 gradient. Leaf-side-specific epicuticular wax deposition (amphiwaxy level) was estimated and related to ASL. KEY RESULTS: In HS species, the CO2 concentration in the adaxial epidermis was lower than in the abaxial one, independently of light conditions. In AS leaves grown in high-light and low-light conditions, the isotopic polarity and CO2 gradient varied in parallel with ASL. The AS leaves grown in high-light conditions increased ASL compared with low light, and δab - δad approached near-zero values. Changes in ASL occurred concomitantly with changes in amphiwaxy level. CONCLUSIONS: Leaf wax isotopic polarity is a newly identified leaf trait, distinguishing between hypo- and amphistomatous species and indicating that increased ASL in sun-exposed AS leaves reduces the CO2 gradient across the leaf mesophyll. Stomata and epicuticular wax deposition follow similar leaf-side patterning.
Keywords: Waxes; vosky; epicuticular wax; izotopy uhlíku; Plant Epidermis; Capsicum annuum; stomata; listy rostlin; Amphistomy; adaxial; cuticle; průduchy rostlin; Carbon Isotopes; Photosynthesis; Plant Leaves; light; fotosyntéza; Carbon Dioxide; photosynthesis; Brassica oleracea; carbon isotope; oxid uhličitý; abaxial; Plant Stomata; epidermis rostlin; leaf internal CO2 concentration